KARAKTERISTIK BURN-UP PADA DISAIN REAKTOR CEPAT BERUKURAN SEDANG DENGAN DAUR ULANG AKTINIDA - Fitriyani (NIM : 20297024), Dian
Abstract : A close cycle simulation is developed for a middle size fast breeder reactor to achiece a core performance optimize, i.e. with actinide recycle. Burnup calculation applied for some model which variated based of the different coolant material (Sodium and Pb-Bi) and of blanket places configuration. The change of atomic density is monitored during core operation and the core always be kept in a critical state by fisil fraction control. The evaluation of calculation result can describe operational requirement such as initial fuel composition, changes in power densities, control reactivity and potential breeding. Calculation result shown that the use Pb-Bi as coolant with blanket are located at the edge of core is better than Sodium for breeding and to reduce coolant void coefficients. But fuel power distribution more stable during the fuel cycle if blanket placed at the centre core, hence core can operated with more long refueling interval.